2004
DOI: 10.1002/jcp.20139
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Fhit gene in the ionizing radiation‐activated ATR/CHK1 pathway

Abstract: Fragile Histidine Triad (Fhit) gene deletion, methylation, and reduced Fhit protein expression occur in about 70% of human epithelial tumors and, in some cancers, are clearly associated with tumor progression. Specific Fhit signal pathways have not been identified, although it has been shown that Fhit overexpression leads to apoptosis in many cancer cell lines. We report in this study that Fhit À/À cells derived from gene knockout mice show much stronger S and G2 checkpoint responses than their wild type count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
3
58
0
Order By: Relevance
“…Inactivation of the phosphatidylinositol 3-kinase/Akt/survivin pathway by Fhit is also implicated in Fhit-mediated apoptosis signaling (20). We assessed previously the Atr-Chk1 pathway in response to mitomycin C, UVC, and ionizing radiation in Fhit-positive and Fhit-negative cells and found that Fhitnegative cells are resistant to apoptosis induced by these genotoxic agents despite activation of the Atr-Chk1 pathway (12,13). The above proteins were not detected by this twodimensional PAGE and MALDI-TOF/MS analysis possibly because differences in protein modification (e.g., phosphorylation and dephosphorylation) or protein structure do not necessarily cause significant mobility differences in twodimensional PAGE gels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of the phosphatidylinositol 3-kinase/Akt/survivin pathway by Fhit is also implicated in Fhit-mediated apoptosis signaling (20). We assessed previously the Atr-Chk1 pathway in response to mitomycin C, UVC, and ionizing radiation in Fhit-positive and Fhit-negative cells and found that Fhitnegative cells are resistant to apoptosis induced by these genotoxic agents despite activation of the Atr-Chk1 pathway (12,13). The above proteins were not detected by this twodimensional PAGE and MALDI-TOF/MS analysis possibly because differences in protein modification (e.g., phosphorylation and dephosphorylation) or protein structure do not necessarily cause significant mobility differences in twodimensional PAGE gels.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last several years, evidence confirming tumor suppressor functions of Fhit has accumulated: Fhit À/À and Fhit +/À mice exhibit increased susceptibility to spontaneous tumors and deletion of a Fhit allele in mice enhances sensitivity to carcinogens, N-nitrosomethylbenzylamine and dimethylnitrosoamine (8)(9)(10)(11); deficiency of Fhit protein decreases sensitivity to DNA-damaging agents, such as mitomycin C, UVC, and ionizing radiation (12,13). Furthermore, overexpression of FHIT by adenoviral gene delivery effectively suppressed cell growth and induced caspase-dependent apoptosis in in vitro and in vivo experiments (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Fhit À/À and Fhit þ /À mice exhibit increased susceptibility to spontaneous tumors and deletion of a Fhit allele in mice enhanced sensitivity to the carcinogen, N-nitrosomethylbenzylamine (NMBA); around 80% of Fhit À/À and Fhit þ /À mice developed forestomach tumors (adenomas, papillomas and invasive carcinomas) after one dose of NMBA, compared with fewer than 8% in wild-type mice (Zanesi et al, 2001;Fujishita et al, 2004). Moreover, deficiency of Fhit protein altered sensitivity to mitomycin C, UVC and ionizing radiation in human gastric carcinoma cells, as well as mouse normal kidney cells, in clonogenic assays (Ottey et al, 2004;Hu et al, 2005). Thus, Fhit plays an important role in tumorigenesis, and FHIT gene therapy is expected to be a novel clinical approach in treatment of human cancers and prevention of tumor development (Dumon et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that FHIT protein is required for enhanced paclitaxel-induced apoptosis. It has been reported that restoration of FHIT protein function undergoes cell cycle arrest and apoptosis in response to some stressful conditions such as those induced by external stimuli, such as serum starvation, 22 Fas treatment, 23 treatment with UVC light or mitomycin C 32 or ionizing radiation 33 better than parental cells lacking FHIT expression, suggesting that usually the FHIT proapoptotic pathway needs activation by stressful agents. Thus, it is not specific to chemotherapeutic agents that FHIT protein facilitates apoptosis in response to pro-apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%